Underweight and obesity are strong predictors of clinical outcomes in patients with ankylosing spondylitis: data from the Smart-phone SpondyloArthritis Management System. (July 2021) - Hu, Lidong; Ji, Xiaojian; Wang, Yiwen; Man, Siliang; Liu, Xingkang; Wang, Lei; Zhu, Jian; Cheng, Jidong; Huang, Feng
Background: The aim of this study was to examine the impact of underweight, overweight and obesity on clinical outcomes and treatment responses to biologics in Chinese patients with ankylosing spondylitis (AS). Methods: Body mass index (BMI) was available in 1074 patients from the Smart-phone SpondyloArthritis Management System. Patients were categorized into four groups based on BMI: underweight, normal weight, overweight and obesity. Multivariable median regression analyses examined the effect of underweight and obesity on clinical outcomes and treatment response to biologics. Results: Among 1074 patients with AS, normal weight accounted for 49.1%, while underweight, overweight, and obesity for 8.1%, 30.1%, and 12.0%, respectively. Compared to patients with normal weight, patients with underweight, overweight and obesity had an increased disease activity, while patients with underweight and obesity had a significantly poor Bath Ankylosing Spondylitis Functional Index and Assessment of Spondyloarthritis International Society Health Index scores. For tumor necrosis factor (TNF)-α inhibitor users, BMI was found to be negatively correlated with changes in disease activity in the multivariate regression model (all p  < 0.05). Besides, the patients using TNF-α inhibitor in the overweight or obesity categories were much less likely to achieve a significant reduction on disease activity during follow-up period in the multivariate regression model (all p  < 0.05), taking these with normal-weight patients as a reference. Conclusions: Both underweight and obesity except for overweight were associated independently with worse disease activity, physical function and health status. Overweight and obesity might impact on treatment responses to biologics in patients with AS. This argues that weight management, to maintain it at a normal level, should be one of the disease management strategies in patients with AS.